1993
DOI: 10.2337/diab.42.12.1799
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of GAD65 and GAD67 in Human, Rat, and Mouse Pancreatic Islets

Abstract: The smaller form of the autoantigen glutamic acid decarboxylase, GAD65 (formerly the 64,000 M(r) autoantigen), is a major target of humoral autoimmunity in type I diabetes. Human autoantisera have been used extensively to characterize the GAD65 antigen in both rat and human islets, but the protein has escaped detection in mouse islets. We have now analyzed the expression of GAD65 and GAD67, the larger glutamic acid decarboxylase protein, in human, rat, and mouse islets of Langerhans and brain, using human mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
115
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 25 publications
8
115
2
Order By: Relevance
“…It has been reported that the expression of GAD65 is under the detectable limit in mouse islets, whereas both rat and human islets express it at significantly higher Development of autoimmune diabetes in glutamic acid decarboxylase 65 (GAD65) 223 levels [8]. In our GAD65 −/− mice, the sudden death before the onset of diabetes might have been caused by severe dysfunction in the central nervous system, consistent with a previous report [9].…”
Section: Discussionsupporting
confidence: 80%
“…It has been reported that the expression of GAD65 is under the detectable limit in mouse islets, whereas both rat and human islets express it at significantly higher Development of autoimmune diabetes in glutamic acid decarboxylase 65 (GAD65) 223 levels [8]. In our GAD65 −/− mice, the sudden death before the onset of diabetes might have been caused by severe dysfunction in the central nervous system, consistent with a previous report [9].…”
Section: Discussionsupporting
confidence: 80%
“…Immunization of young NOD mice with human GAD65, the main immunogenic isoform of glutamate decarboxylase in human type 1 diabetes [24], can reduce the incidence of diabetes [7,8,[11][12][13][14]. Similar prevention was also obtained by immunization with the other isoform, GAD67 [10], which is predominant in mouse islets [25,26] and highly expressed [20] and modulable [22] in the NOD mouse. A limited number of peptides derived from the COOH terminus of the human GAD65 protein have been shown to stimulate in vitro the proliferation of splenic cells from young prediabetic NOD mice [7].…”
Section: Discussionmentioning
confidence: 95%
“…Human islets only express the GAD6s protein [24,25] and the incidence of GAD67 antibodies in IDDM is low [26,27]. GAD67 does not seem to have an independent role as an autoantigen in IDDM.…”
mentioning
confidence: 99%
“…In addition to GAD6s, GAD is expressed as a second non-allelic form, GAD67 in neurons [23] and in rat and mouse beta cells [24]. Human islets only express the GAD6s protein [24,25] and the incidence of GAD67 antibodies in IDDM is low [26,27].…”
mentioning
confidence: 99%